Axiidean ghost shrimps (Decapoda: Axiidae, Callianassidae, Callichiridae, Micheleidae) of the Trindade and Martin Vaz Archipelago, Vitória-Trindade Seamounts Chain and Abrolhos, off southeastern Brazil - Pachelle, Paulo P.g.; Tavares, Marcos (Zootaxa, 2020)
The Trindade and Martin Vaz (TMV) volcanic archipelago is highly isolated, being located some 1200 km off the Brazilian coast and about 4200 km away from the nearest African coast. The only axiidean known from the archipelago is Coralaxius nodulosus (Meinert, 1877), a species extensively reported in the western Atlantic. From 2012 to 2018, 263 SCUBA diving and intertidal samplings were conducted at TMV and yielded 46 axiidean specimens in three species, one of which is a new species: Corallianassa longiventris (A. Milne-Edwards, 1870), Neocallichirus grandimana (Gibbes, 1850), and Fragillianassa joeli sp. nov., a species closely related to F. fragilis (Biffar, 1970). Hitherto unreported specimens from along the Vitória-Trindade Seamounts Chain (VTSC) and the Abrolhos Bank were also included in this report, namely C. nodulosus and Michelea vandoverae (Gore, 1987). The occurrence of M. vandoverae at the Abrolhos Bank extends its range into the southwestern Atlantic. Coralaxius abelei Kensley & Gore, 1981 is herein considered a junior synonym of Coralaxius nodulosus (Meinert, 1877). Meinertaxius Sakai, 2011, therefore becomes a subjective synonym of Coralaxius Kensley & Gore, 1981. Axiideans from the tropical southern-central Atlantic oceanic islands (Ascension, Fernando de Noronha, Rocas Atoll, Saint Helena, Trindade and Martin Vaz) are listed with their gross distribution in the Atlantic Ocean revealing a strongly depauperate axiidean insular fauna, totaling six species. Except for Axiopsis serratifrons (A. Milne-Edwards, 1873), a pantropical species, the insular southwestern-central Atlantic axiideans are entirely of western Atlantic affinities, with F. joeli sp. nov. being the only endemic so far.